2017
DOI: 10.3906/sag-1512-69
|View full text |Cite
|
Sign up to set email alerts
|

Performing ICSI with commercial microinjection pipettes enhanced pregnancy rates

Abstract: Background/aim: Many technical factors can affect intracytoplasmic sperm injection (ICSI) outcomes. The role of the injection micropipette could be of vital importance in ICSI programs. The main goal was to compare ICSI pregnancy outcomes between commercial and home-made injection micropipettes in a large population with male factor infertility.Materials and methods: Five-hundred and eleven ICSI cycles with severe male factor were included in this retrospective study. ICSI cycles were divided into two groups: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The lower incidence of degeneration and the higher normal fertilization rate and better embryo development and faster cleavage from ICSI using the smallest-diameter (3-5 µm) injection pipette was likely a result of minimized degree of the mechanical trauma exerted on the oolemma, minimized amount of ooplasm aspirated into the injection pipette prior to injection, and minimized the amount of PVP injected into the oocyte along with the spermatozoon [33]. At the time of oolemma breakage, reducing the volume of aspirated cytoplasm into the injection pipette can improve the ICSI success rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower incidence of degeneration and the higher normal fertilization rate and better embryo development and faster cleavage from ICSI using the smallest-diameter (3-5 µm) injection pipette was likely a result of minimized degree of the mechanical trauma exerted on the oolemma, minimized amount of ooplasm aspirated into the injection pipette prior to injection, and minimized the amount of PVP injected into the oocyte along with the spermatozoon [33]. At the time of oolemma breakage, reducing the volume of aspirated cytoplasm into the injection pipette can improve the ICSI success rate.…”
Section: Discussionmentioning
confidence: 99%
“…Khalili and teammate indicated that pregnancy improves when commercial injection micropipettes are used in ICSI program. They compared ICSI outcome using commercial versus home-made injection micropipettes in a large population with severe male infertility [33].…”
Section: Micro Toolsmentioning
confidence: 99%
“…Puncture needle, solid millineedle, is an indispensable medical device in medical surgery [140], which have been widely used for tissue puncture, tissue extraction and so on [141]. For example, doctors can get an accurate and reliable diagnosis by puncturing the tissue with puncture needle to analyze the intrinsic differences in tissue cells [142].…”
Section: Millineedles For Puncturementioning
confidence: 99%